RESEARCH AND EXPERIMENTAL APPROBATION OF PEDAGOGICAL TERMS FOR THE FORMATION OF STUDENTS’ LEADERSHIP SKILLS IN THE INNOVATIVE EDUCATIONAL ENVIRONMENT OF THE LYCEUM - Iermak Tetiana (Вісник Університету імені Альфреда Нобеля. Серія Педагогіка і психология, 2023)
The study reveals the problem of the formation of leadership skills in students of general secondary education institutions. The article aims to investigate the technique of formation of students’ leadership skills in the innovative educational environment of the lyceum. The research used both theoretical methods (analysis, generalization, modelling and design), and empirical methods, among which the pedagogical experiment was the leading one. It has been found that leadership skills are essentially a set of stable personality characteristics that ensure the effectiveness of activities and aid in taking the position of a leader in a group, are manifested in organizational skills, and can significantly influence the behaviour and mood of people, allow being an example for imitation. Leadership skills of students of general secondary education institutions are presented as a system of four groups – personal, cognitive, social and civic skills. The criteria for the formation of students’ leadership skills have been identified, among which are motivational, cognitive, activity-based and evaluative-reflective ones. During the diagnostic experiment the lack of students’ leadership skills according to certain components and criteria was recorded. It has been emphasized that removing the causes and difficulties in the formation of students’ leadership skills is possible if certain pedagogical terms are observed. These are the following: the development of student’s motivation for the formation of leadership skills; the shaping of an educational environment focused on the formation of students’ leadership skills; the creation of educational and methodical support for the formation of leadership skills; elaboration of the school’s partnership with stakeholders. The content of the research-experimental approbation of pedagogical conditions for the formation of students’ leadership skills was disclosed. The substance of the complex technique, which ensured the creation in the educational process of the lyceum of certain pedagogical terms for the formation of leadership skills in students, was outlined. The complex technique was implemented throughout the motivational-preparatory, developmental, formative, and control-corrective stages. In consequence of the approbation, pedagogical terms and tools for the leadership skills formation in students have been developed and implemented, namely: information, computer and Internet technologies, cases, projects, test methods, portfolios, business games, role-playing, situational and simulation games, brainstorming, interactive methods, student self-government, briefing, debate; the concept of an educational and developmental environment focused on the formation of students’ leadership skills; forms of work to shape leadership skills in students: thematic lessons, training, virtual and thematic excursions, club work, electives, senior school leaders’ summit, round table, charity events, volunteer work; methodical support for the formation of teachers’ readiness to educate students’ leadership qualities: training classes “7 habits of highly effective people”, training session “Formation of leadership skills” (12 hours); methods of stimulating students to leadership and leadership behaviour via educational situations (cognitive, evaluative, and alternative ones), technologies for creating a situation of success, project activities; a package of methodical support to assist teachers, parents and the public in the formation of leadership qualities in students. Based on the results of qualitative, quantitative and statistical analysis, the effectiveness of the developed pedagogical terms for the formation of leadership skills in students in the innovative environment of the lyceum has been proven.